2016
DOI: 10.5194/isprs-annals-iii-7-257-2016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Viewing Geometry Within Hyperspectral Images Retrieved From Uav Snapshot Cameras

Abstract: ABSTRACT:Hyperspectral data has great potential for vegetation parameter retrieval. However, due to angular effects resulting from different sunsurface-sensor geometries, objects might appear differently depending on the position of an object within the field of view of a sensor. Recently, lightweight snapshot cameras have been introduced, which capture hyperspectral information in two spatial and one spectral dimension and can be mounted on unmanned aerial vehicles. This study investigates the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results of Burkart et al (2015) showed differences in three vegetation indices by considering different geometries of view in a wheat study site. Lastly, Aasen (2016) published results about uncorrected BRDF effects and showed different spectral responses and different normalized difference vegetation index values for a barley field. These results highlight the importance of the correction of BRDF effects.…”
Section: Comparison and Outlookmentioning
confidence: 99%
“…The results of Burkart et al (2015) showed differences in three vegetation indices by considering different geometries of view in a wheat study site. Lastly, Aasen (2016) published results about uncorrected BRDF effects and showed different spectral responses and different normalized difference vegetation index values for a barley field. These results highlight the importance of the correction of BRDF effects.…”
Section: Comparison and Outlookmentioning
confidence: 99%
“…But when an orthomosaic is generated from multiple overlapping images, each area of interest on the ground (e.g., a plot) is captured by multiple images with different viewing geometries and several options exist to extract the signature of this area (Aasen and Bolten, 2018). It has been shown that the different data processing and extraction approaches have an influence on the apparent reflectance in remote sensing data in the visible and nearinfrared, e.g., (Aasen, 2016;Aasen and Bolten, 2018). This results from the interaction of surface anisotropy (meaning that the signal is directionality dependent) and measurement geometry [expressed by the bi-directional reflectance distribution function; BRDF, (Nicodemus et al, 1977;Schaepman-Strub et al, 2006)], which also effects the apparent temperature (Jones et al, 2009;Cao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%